Integrated indicator framework and methodology for monitoring and assessment of hazardous substances and their effects in the marine environment. (March 2017) - Vethaak, A. Dick; Davies, Ian M.; Thain, John E.; Gubbins, Matthew J.; Martínez-Gómez, Concepción; Robinson, Craig D.; Moffat, Colin F.; Burgeot, Thierry; Maes, Thomas; Wosniok, Werner; Giltrap, Michelle; Lang, Thomas; et al.
Abstract: Many maritime countries in Europe have implemented marine environmental monitoring programmes which include the measurement of chemical contaminants and related biological effects. How best to integrate data obtained in these two types of monitoring into meaningful assessments has been the subject of recent efforts by the International Council for Exploration of the Sea (ICES) Expert Groups. Work within these groups has concentrated on defining a core set of chemical and biological endpoints that can be used across maritime areas, defining confounding factors, supporting parameters and protocols for measurement. The framework comprised markers for concentrations of, exposure to and effects from, contaminants. Most importantly, assessment criteria for biological effect measurements have been set and the framework suggests how these measurements can be used in an integrated manner alongside contaminant measurements in biota, sediments and potentially water. Output from this process resulted in OSPAR Commission (www.ospar.org ) guidelines that were adopted in 2012 on a trial basis for a period of 3 years. The developed assessment framework can furthermore provide a suitable approach for the assessment of Good Environmental Status (GES) for Descriptor 8 of the European Union (EU) Marine Strategy Framework Directive (MSFD). Graphical abstract: Highlights: An integrated framework for marine contaminants and their effects is developed. Determinants for sediment, fish, and shellfish with assessment criteria are provided. A multistep traffic light data aggregation tool is proposed and demonstrated. It resulted in OSPAR guidelines for integrated chemical-biological effect monitoring. The approach could be useful for determination of GES for Descriptor 8 of MSFD.